BAHASA, PIKIRAN, DAN DUNIA DALAM PERSPEKTIF LINGUISTIC RELATIVITY PRINCIPLE BENJAMIN LEE WHORF DAN LANGUAGE GAME LUDWIG WITTGENSTEIN - Basuki, Irawan Santoso Suryo (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Language is the one of many tools by which humans express ideas, images, and understanding of the world. However, the position of language between mind and world remains unclear. The question arises on whether language affects the way humans perceive the reality around them or, on the contrary, the reality that affects people's thoughts about the world. This article aims to examine the issue of language position between the mind and the world by conducting a comparative study of the Linguistic Relativity Principle offered by Benjamin Lee Whorf and the Language Game proposed by Ludwig Wittgenstein. Literature study was carried out by examining Wittgenstein's magnum opus Philosophical Investigations and Whorf's influential work Language, Thought and Reality. This article finds that the position of language is not between the mind and the world, but both transcends and encompasses them The key between thought and reality, mind and world, is the two-way relationship that is governed by it.